2010
DOI: 10.1002/micr.20776
|View full text |Cite
|
Sign up to set email alerts
|

The effect of supporting a surgeon's wrist on their hand tremor

Abstract: Supporting the wrists significantly decreases the amplitude of the tremor. Surgeons should consider using wrist supports when performing parts of operations which necessitate a high degree of accuracy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 8 publications
1
25
1
Order By: Relevance
“…In line with others [Coulson et al, 2010;Murbe et al, 2001], we observed that the support of the free hand by the contralateral hand or as a two-point support has a significant effect on the maximum amplitude and the peak frequency of deviations.…”
Section: Discussionsupporting
confidence: 73%
“…In line with others [Coulson et al, 2010;Murbe et al, 2001], we observed that the support of the free hand by the contralateral hand or as a two-point support has a significant effect on the maximum amplitude and the peak frequency of deviations.…”
Section: Discussionsupporting
confidence: 73%
“…For the manual and commercial tool techniques, the operator's hands were supported on a flexible arm with a metal bar similarly to a Yasargil bar as it has been shown that supporting the wrists significantly decreases the amplitude of the tremor [12]. Force measurement was coupled to video recording through the microscope to collect force data from the beginning to the end of the insertion only.…”
Section: Methodsmentioning
confidence: 99%
“…Enhanced physiologic tremor may be stimulated by anxiety, stress, fatigue, medications, and metabolic derangements such as hyperthyroidism, hypoglycemia, and hypothermia,50 potentially useful variables to assess in the evaluation of patients with MEM. The phenomenon of enhanced physiologic tremor from exertion is particularly relevant to the specialists often diagnosing MEM: otolaryngologists are studying how to improve manual precision impaired by tremor during prolonged microsurgery 6264…”
Section: Discussionmentioning
confidence: 99%